LONG TERM CARE INSURANCE WITH MULTISTATE DISCRETE MARKOV MODEL APPROACH - RAMADHANIS (NIM: 20816018), FITRI
This thesis is written to determine the amount of premium that will be paid by the insured and the amount of reserve from long term care (LTC) insurance. LTC insurance is insurance for the insured who has a chronic disease. Chronicity or malignancy of a disease will increase as the insured get older. The change in malignancy is modelled with multistate discrete markov which consist of 3-states namely state of health, illness, death and 4-state namely state of health, illness I, illness II, death. With this multistate model it is possible to calculate the amount of premium and the amount of reserve based on state. The assumption used is that the sick insured cannot return to health and the calculation is based on mortality from the Indonesian Mortality Table data (TM III) in 2011. From the result of this simulation there is a potential that the increase in the number of states may decrease the amount of premium and the amount of reserve.